ANTIOXIDANT ACTIVITY TESTING AND DETERMINATION OF SPF VALUE IN VITRO EXTRACT OF HAIR FRUIT SKIN (Nephelium lappaceum), MANGOS (Garcinia mangostana) AND DURIAN (Durio zibethinus) - Yola Desnera Putri; Deby Tristiyanti; Aneu Nurdiana (Borneo Journal of Pharmascientech, 2019)
ABSTRACT Rambutan rind, mangosteen rind, and durian rind contain phenolic compounds and flavonoids that have high antioxidant activity, also thought to be efficacious as a sunscreen. The aims of this research was to determined the antioxidant activity and the SPF of sunscreen ethanol extract of mangosteen rind (Garcinia mangostana), rambutans rind (Nephelium lappaceum) and durian rind (Durio zibethinus). The extraction method was used maceration method using ethanol 96%. DPPH (1, 1- diphenyl-2-picrylhidrazil) was used to determine the antioxidant activity. The effectiveness of sunscreen was done by determine the SPF value in vitro using spectrophotometric method. The results showed that the three ethanol extracts containing phenolic compounds and flavonoids. Those compounds have antioxidant activity and also sunscreen, the highest antioxidant activity owned by ethanol extracts of rambutan rind with the value IC50 amounting to 2,697 ppm, second are ethanol extracts of mangosteen rind with IC50 amounting to 2,710 ppm and lastly, ethanol extracts of durian rind with the value IC50 amounted to 11.398 ppm, whereas for the highest SPF value owned by the ethanol extract of mangosteen rind 29.008, then ethanol extract rind of rambutans at 9.99. Both of ethanol extract rinds have a high antioxidant activity and potential to be used as active ingredients in sunscreen preparations, while to extract durian rind ethanol does not have the ability as sunscreen because the SPF value was 0.967. Keywords : Garcinia mangostana, Nephelium lappaceum, Durio zibethinus, antioxidant, sunscreen